Diagnosis of teenager’s personal anxiety in educational activities (Revista de Investigaciones Universidad del Quindío, 2022)
The paper provides a theoretical and analytical review of modern methods of diagnosing anxiety states and personal anxiety, which have been used by Russian scientists in recent years. The paper presents the arguments of scientists about the nature and psychological and pedagogical characteristics of personal anxiety as a property of personality, mental state and character traits. The paper describes the scientific apparatus and methodological tools of diagnostic procedures. The methods used in the study (observation, survey, analysis of the products of educational activity, Spielberg-Khanin’s method of personal and situational anxiety, the J. Taylor’s method of measuring the level of anxiety, the method “Multidimensional assessment of child anxiety” (MACA), statistical methods of data processing are highlighted and the empirical results are discussed. The results  indicat that it is necessary to separate the scientific concepts of anxiety and uneasiness as non-fundamental and having a different psychological and physiological basis.
Keywords: Personality; Teenager; Educational activity; Personal anxiety (Pa); Situational anxiety (SA)